Visualizing Fascism : The Twentieth-Century Rise of the Global Right - Thomas, Julia Adeney, 1958-; Eley, Geoff, 1949- (Book collections on Project MUSE., 2020)
"Visualizing Fascism explores various ways of tracing, displaying, viewing, and interacting with fascism, examining fascism as both a global and aesthetic phenomenon during the twentieth century. It emphasizes transnational and visual qualities in order to refigure ways of establishing visual languages, articulate commentaries on the dynamic nature of national identity, and form both supportive and challenging attitudes about the global right. In particular, this volume seeks to challenge the notion that fascism is primarily a national product of Italy, Japan, and Germany; rather it seeks to locate the rise of fascism and the global right in transnational networks connected by capitalism and imperialism. The collection contains twelve essays. In the introduction, Thomas examines the rise of global and aesthetic forms of fascism, ending with the formulation of the "portable concept of fascism"--Wherein fascism is defined more by its "energies" and "ideologies" than by its local manifestations. In two of the volume's early essays, Maggie Clinton and Paul D. Barclay examine the use of public imagery-modernist visuals in interwar China, and chureito, or loyal-spirit towers, in Japan-to envision and shore up support for nationalist ideologies. In her essay, Ruth Ben-Ghiat challenges the fascist objective to erase the agency of the individual in favor of the undifferentiated mass by examining images of faces taken from everyday life under fascist regimes. In another essay, Lorena Rizzo investigates fascist and imperialist entanglement in Southern Africa by examining photographs of settler colonialism in Namibia. The later essays historicize the interconnected visual and historical lineages within the Netherlands, Japan, Indonesia, Slovakia, and Spain-contexts that combine to create a common vocabulary for national identity making. In these essays, Ethan Mark, Bertrand Metton, and Nadya Bair investigate the actors and methods integral to creating a joint foundation for fascist aesthetics. In the second to last essay, Claire Zimmerman addresses the ways in which national and regional narrative building contributes to establishing various futures, accounting for the importance of understanding the implications behind elements of style and image when examining the visual rhetoric of fascism. This collection will be particularly suited to students"--